Spinopelvic challenges in primary total hip arthroplasty - Grammatopoulos, George; Innmann, Moritz Maximilian; Phan, Philippe; Bodner, Russell; Meermans, Geert (EFORT open reviews, 2023)
There is no universal safe zone for cup orientation. Patients with spinal arthrodesis or a degenerative lumbar spine are at increased risk of dislocation. The relative contributions of the hip (femur and acetabulum) and of the spine (lumbar spine) in body motion must be considered together. The pelvis links the two and influences both acetabular orientation (i.e. hip flexion/extension) and sagittal balance/lumbar lordosis (i.e. spine flexion/extension). Examination of the spino-pelvic motion can be done through clinical examination and standard radiographs or stereographic imaging. A single, lateral, standing spinopelvic radiograph would be able to providemost relevant information required for screening and pre-operative planning. A significant variability in static and dynamic spinopelvic characteristics exists amongst healthy volunteers without known spinal or hip pathology. The stiff, arthritic, hip leads to greater changes in pelvic tilt (changes are almost doubled), with associated obligatory change in lumbar lordosis to maintain upright posture (lumbar lordosis is reduced to counterbalance for the reduction in sacral slope). Following total hip arthroplasty and restoration of hip flexion, spinopelvic characteristics tend to change/normalize (to age-matched healthy volunteers). The static spinopelvic parameters that are directly associated with increased risk of dislocation are lumbo-pelvic mismatch (pelvic incidence - lumbar lordosis angle >10°), high pelvic tilt (>19°), and low sacral slope when standing. A high combined sagittal index (CSI) when standing (>245°) is associated with increased risk of anterior instability, whilst low CSI when standing (<205°) is associated with increased risk of posterior instability. Aiming to achieve an optimum CSI when standing within 205-245° (with narrower target for those with spinal disease) whilst ensuring the coronal targets of cup orientation targets are achieved (inclination/version of 40/20 ±10°) is our preferred method.